SPG11 presenting with dystonic tremor in childhood. (June 2022) - Innes, Emily A.; Goetti, Robert; Mahant, Neil; Ho, Gladys; Williams, Laura; Gill, Deepak; Dale, Russell C.; Mohammad, Shekeeb S.
Abstract: This is a unique case of SPG11 mutation presenting as childhood onset dystonic tremor without weakness or spastic paraplegia. Hereditary spastic paraplegia is the most common phenotype of SPG11 mutation though there are reports of an extended phenotype of SPG11 including dopa-responsive dystonia and tremor. Highlights: The most common phenotype of SPG11 is hereditary spastic paraplegia (HSP). Tremor and dystonia can be presenting symptoms of SPG11 without HSP, lower motor neuron abnormalities or parkinsonism. "Ears of lynx" and thin corpus callosum are imaging signs that are suggestive yet not entirely specific for SPG11.